2006
DOI: 10.1152/ajpcell.00248.2005
|View full text |Cite
|
Sign up to set email alerts
|

Potential of fibroblasts to regulate the formation of three-dimensional vessel-like structures from endothelial cells in vitro

Abstract: The development of vessel-like structures in vitro to mimic as well as to realize the possibility of tissue-engineered small vascular networks presents a major challenge to cell biologists and biotechnologists. We aimed to establish a three-dimensional (3-D) culture system with an endothelial network that does not require artificial substrates or ECM compounds. By using human skin fibroblasts and endothelial cells (ECs) from the human umbilical vein (HUVECs) in diverse spheroid coculture strategies, we verifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
121
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 53 publications
5
121
0
1
Order By: Relevance
“…Furthermore, the development of vasculature in vitro was stimulated by physiological doses of LH, FGF2 and VEGFA. While a number of cell culture systems have been developed to investigate angiogenesis, the vast majority use a combination of cell lines such as human umbilical vein endothelial cells (HUVECs) or bovine aortic endothelial cells (BAEC) with human fibroblasts (Bishop et al 1999, Kunz-Schughart et al 2006) rather than primaryderived cells. While these systems provide an invaluable tool to screen potential pro-and anti-angiogenic compounds for use in tissue repair and treatment of diseases such as cancer, they are less relevant to study the physiological mechanisms controlling angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the development of vasculature in vitro was stimulated by physiological doses of LH, FGF2 and VEGFA. While a number of cell culture systems have been developed to investigate angiogenesis, the vast majority use a combination of cell lines such as human umbilical vein endothelial cells (HUVECs) or bovine aortic endothelial cells (BAEC) with human fibroblasts (Bishop et al 1999, Kunz-Schughart et al 2006) rather than primaryderived cells. While these systems provide an invaluable tool to screen potential pro-and anti-angiogenic compounds for use in tissue repair and treatment of diseases such as cancer, they are less relevant to study the physiological mechanisms controlling angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…24 Understanding this process remains a challenge, since fibroblasts have the capacity to alter the mechanical extracellular microenvironment, thereby regulating vascularization processes. 25 Fibroblast-derived proteins, including growth factors and matrix proteins, have been shown to modulate EC sprouting and the expansion of capillary-like networks in vitro, [26][27][28] contributing to the role of fibroblasts as periendothelial cells in vivo. 29 Thus, the hypothesis underlying herein is that, when cocultured with OECs or mature ECs, different types of fibroblasts will exert distinct influences in the assembly of capillary-like structures.…”
mentioning
confidence: 99%
“…Tissue engineering-based research in both two-dimensional (2D) and three-dimensional cocultures in vitro revealed that the active interaction between ECs and MSCs (or osteoprogenitor and fibroblast) induced the formation of tube-like cell aggregation structures. This result indicates that angiogenesis and prevascularization are involved in the cellcell communication and remodeling of the functional blood vessel development in vivo [5,[18][19][20][21][22][23][24][25][26]. Moreover, MSCs could repress ECs by regulating cytokine-induced leukocyte recruitment [27], while the activated ECs could regulate the MSCs-to-ECs transmigration in a leukocyte-like mechanism [28,29].…”
mentioning
confidence: 99%